A textbook on commented reading of scientific texts for foreign students-humanitarians of preparatory departments: a linguodidactic model - Швець, Г. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2017)
The problem of teaching Ukrainian as a language of the future speciality to foreign students of preparatory departments has been raised in the article. The formation of scientific speech skills at a sufficient level determines the success of foreigners’ training at Ukrainian universities. Full participation in the education process is possible if a student knows the scientific style of speech: he can effectively listen to lectures, study scientific and educational literature, take part in practical courses and seminars, write essays, term papers and dissertations. Therefore, the author stresses the necessity of creating textbooks, aimed at the formation and development of scientific speech skills of foreign students who study at preparatory departments.The article outlines the situation with the organization of preparatory teaching students- humanitarians. It has been emphasized that the central problem in the organization of training of foreign students-humanitarians to study at Ukrainian universities is an ignoring specifics of various humanitarian areas: one curriculum combines humanitarian, social and creative specialties. The paper presents linguodidactic strategy for developing scientific speech skills of foreign students-humanitarians. An important element of this strategy is a training course, which gives students an idea of the scientific style of speech and trains them to percept specific disciplines. This can be the basis of scientific style of speech or commented reading of scientific texts.The article identifies the following components of alinguodidactic model of the textbook on commented reading of scientific texts for foreign students-humanitarians of preparatory departments: training texts, based on linguistic features of the humanities’ language and the teaching principles of accessibility, concentric presentation of training material, interdisciplinary coordination; system of tasks to modeled texts aimed at creating scientific speech skills; optimal architectonic of a textbook (texts for collective and individual reading, terminology dictionary, a list of common scientific phrases); effective semiotics and printing code (tables, rules, fonts, etc.).